Ex vivo mass spectrometry-based biodistribution analysis of an antibody-Resiquimod conjugate bearing a protease-cleavable and acid-labile linker - Bisbal Lopez, Lydia; Ravazza, Domenico; Bocci, Matilde; Zana, Aureliano; Principi, Lucrezia; Dakhel Plaza, Sheila; Galbiati, Andrea; Gilardoni, Ettore; Scheuermann, Jörg; Neri, Dario; Pignataro, Luca; Gennari, Cesare; et al. (Frontiers in Pharmacology, 2023)
Immune-stimulating antibody conjugates (ISACs) equipped with imidazoquinoline (IMD) payloads can stimulate endogenous immune cells to kill cancer cells, ultimately inducing long-lasting anticancer effects. A novel ISAC was designed, featuring the IMD Resiquimod (R848), a tumor-targeting antibody specific for Carbonic Anhydrase IX (CAIX) and the protease-cleavable Val-Cit-PABC linker. In vitro stability analysis showed not only R848 release in the presence of the protease Cathepsin B but also under acidic conditions. The ex vivo mass spectrometry-based biodistribution data confirmed the low stability of the linker-drug connection while highlighting the selective accumulation of the IgG in tumors and its long circulatory half-life.